O-207 Incidence of Y chromosome microdeletions and microdissection testicular sperm extraction (micro TESE) in patients with Japanese azoospermic patients. (30th June 2022) - Ishikawa, T; Mizuta, S; Yamaguchi, K; Ohara, Y; Doshida, M; Takeuchi, T; Matsubayashi, H
Abstract: Study question: What is the frequency of azoospermia factor (AZF) microdeletions and sperm retrieval rate (SRR) by micro TESE in patients with these deletions? Summary answer: AZFc is most frequent of Y chromosome microdeletions and a predictor of micro TESE outcome in Japanese azoospermic men. What is known already: After Klinefelter syndrome, Y chromosome microdeletions are the second most frequent genetic cause of male infertility, with a prevalence of 2%-10% in non‐obstructive azoospermia (NOA) and three spermatogenesis loci in the Y chromosome long arm (Yq11) have been classified as AZFa, AZFb, and AZFc. The classical correlation of histopathology phenotypes with these three microdeletions comprises of complete absence of germ cells (Sertoli cell‐only syndrome) in patients with AZFa microdeletions, maturation arrest of meiosis in patients with AZFb microdeletions, and hypospermatogenesis in patients with AZFc microdeletions, however, individual variation in the extent of deletions has led to various spermatogenic phenotypes. Study design, size, duration: We performed a retrospective study based on two reproduction centers in Japan and evaluated 1373 azoospermic patients in our clinics between September 2013 and December 2021. We investigated the frequency of AZF microdeletions and SRR by micro TESE in patients with these microdeletions and therefore aimed to evaluate the correlation between AZF microdeletions and micro TESE results. Participants/materials, setting, methods: A total of 1373 azoospermic were enrolled. After the diagnosis of azoospermia, karyotype analysis and detection of Y chromosome microdeletions were performed on peripheral blood lymphocytes of these patients. Y chromosome microdeletions in AZFa, AZFb, and AZFc regions were detected using Promega Y Chromosome AZF Analysis System version 2.0 (Promega Co.). Twenty sequence‐tagged sites within the AZF region of Yq11 and the sex‐determining region Y gene were targeted for polymerase chain reaction (PCR) amplification. Main results and the role of chance: One hundred and fifty‐two AZF microdeletions (11.1%) were detected in the azoospermic patients. The most common deleted region was AZFc (60 cases, 4.4%). Among the patients, 17 (1.2%), 1 (0.1%), 42 (3.1%), 13 (1.0%), and 6 (0.5%) had AZFa, AZFa+b, AZFb+c, AZFb, and AZFa+b+c microdeletions, respectively. When the cases were grouped according to causes of infertility that could be detected, no Y chromosome microdeletions were detected in some groups (cases with Klinefelter Syndrome, hypogonadotropic hypogonadism, congenital absence of vas deferens, and 47, XYY karyotype). Fifty-three azoospermic men with AZFc microdeletions underwent micro TESE, and spermatozoa were detected in 88.7% (47/53) of these men. In contrast, we detected spermatozoa in only 20.4% (109/534) of the azoospermic men without AZF microdeletions. The SRR was much higher in patients with AZFc microdeletions than that of patients without AZF deletions. Although three azoospermic men with AZFb+c microdeletions had also undergone micro TESE following patient request, we did not retrieve spermatozoa. Limitations, reasons for caution: We excluded post chemotherapy NOA showing 46, XX and AZFa+b+c deletions post bone marrow transplantation from female donor. Additionally, we did not detect AZFc partial deletion including gr/gr deletion. The cohort size of this study is not small, however, our screened population of infertile men may be biased. Wider implications of the findings: NOA patients with AZFc microdeletions had a high percentage of successful sperm retrieval by micro TESE. Our study emphasizes that diagnosis of Y chromosome microdeletions is critical for preconception genetic counseling and provides clinically valuable prognostic information to couples considering surgical sperm retrieval. Trial registration number: None